Nursing interventions for stress and burnout among professional athletes: A narrative review - Thomas, J. (Journal of Sports and Rehabilitation Sciences, 2026)
Professional athletes endure immense physical and psychological demands that predispose them to stress and burnout. The combination of high-performance expectations, rigorous training, frequent competitions, media scrutiny, and career uncertainties places athletes at significant risk for mental health challenges. Stress and burnout not only impair performance but also contribute to long-term psychological and physical consequences. Nursing interventions play a critical role in addressing these issues through holistic care, early detection, mental health support, stress management strategies, lifestyle education, and rehabilitation programs. This article explores the etiology and manifestations of stress and burnout among professional athletes, examines evidence-based nursing interventions, and highlights the role of mental health and sports nurses in promoting resilience, recovery, and overall well-being. Professional athletes are at significant risk for stress and burnout due to the demanding nature of competitive sports. Stress, if unmanaged, leads to burnout, impairing performance, mental health, and overall quality of life. Nurses play a pivotal role in addressing these challenges through holistic interventions, including stress management strategies, lifestyle education, psychological support, and interprofessional collaboration. Nursing interventions such as cognitive-behavioral strategies, relaxation techniques, sleep hygiene, and psychoeducation are effective in preventing and managing stress and burnout. By recognizing early warning signs and providing continuous support, nurses safeguard both the mental health and career longevity of athletes. The integration of mental health nursing into sports organizations is not only beneficial but also essential for the sustainable well-being and performance of athletes. By integrating psychological support, health education, lifestyle management, and collaborative care models, nurses can significantly mitigate the impact of stress and burnout in professional sports.